Предмет: Алгебра,
автор: biztimka246
5х^2+5x-15=2x^2+11x+9
Ответы
Автор ответа:
0
3x^2-6x-24=0
x1=-2
x2=4
x1=-2
x2=4
Автор ответа:
0
5х^2+5x-15=2x^2+11x+9
5х^2+5x-15-2х^2-11х-9=0
3х^2-6х-24=0 можно сократить на 3 и получится,
х^2-2-8=0
D=4-4*1*(-8)=36 D=6
х₁=(2+6)/2=4
х₂=(2-6)/2= -2
5х^2+5x-15-2х^2-11х-9=0
3х^2-6х-24=0 можно сократить на 3 и получится,
х^2-2-8=0
D=4-4*1*(-8)=36 D=6
х₁=(2+6)/2=4
х₂=(2-6)/2= -2
Интересные вопросы
Предмет: Химия,
автор: andrianamicka5
Предмет: Математика,
автор: aluakalmenova4
Предмет: Другие предметы,
автор: bogbangoyan009
Предмет: Физика,
автор: champions
Предмет: Алгебра,
автор: Hatige